Influence and challenge of COVID-19 in forensic identification - Bin Cong; Xin Liu (Wolters Kluwer Medknow Publications, 2020)
During the COVID-19 epidemic, the professionals in the field of forensic pathology, forensic sciences in general, and clinical forensic medicine have been performing medicolegal investigation in their communities. The forensic medical personnel who carry out such investigation/identification are facing a great risk of potential infection. Therefore, forensic institutions and forensic examiners should improve their awareness of infection risk and take universal precautions to prevent infection and spread of coronavirus. In addition, forensic experts should abide by the laws when they deal with social unrest and also strengthen research on COVID-19-related medical issues.